Malignant hemangiopericytoma a abdominal location. Presentation of two cases - Barozzi, Carlos; Boudrandi, Sonia; Rondán, Mariella; Vercelli, Jorge; Miegge, Laura; Fleitas, Gabriela; Ruso, Luis (Cirugía del Uruguay, 1996)
Hemangiopericytomas constitute a neop/asic proliferation of the pericytes. They were described far the first time by Stout and Murray in 1942. They can appear in any part of the organism but are infrequent in the sp/achnic area. They are tumors with variable biologica/ conduct. Local recidive, development of methastases, high mithotic rafe and the presence of necrosis and hemorrhage are elements of bad prognosis. This paper presents two cases of malignant hemangiopericytomas of,abdominal /ocalization, both of mesial origin. The pretended onco/ogical resection of one of them and the diagnostica/ /aparotomy in the stage of secondary liver in the other coincide with different histopatological and evolutive patterns. At present, surgery is the only efficient therapeutical option far these tumors; radiotherapy and chemotherapy have poor results